Analytical and Numerical Solutions of Linear Volterra Integral Equations of the Second Kind with Weakly Singular Kernel by using the Sixth Order of Non_polynomial Spline Functions by Matlab (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Volterra Integral Equations has wide range of the applications in physics andengineering problems.Spline function can be integrated and differentiated due to being piecewise polynomials and can easily store and implemented on digital computers, nonpolynomialspline function apiece wise is a blend of trigonometric, as well as ,polynomialbasis function ,which form a complete extended Chebyshev space.Matlab is a high-levelsoftware package with many built in functions that make the learning of numerical methodsmuch easier and interesting.The aims of this paper is to focus and use the sixth order nonpolynomialspline functions to solve linear Voltera integral equations with Weakly SingularKernel. We followed the applied numerical method using Matlab .Numerical examples arepresented to illustrate the applications of this method and to compare the computed resultswith other numerical methods for exact solutions.